PENGARUH FITUR KATEGORISASI PENGELUARAN OTOMATIS PADA MOBILE BANKING TERHADAP PERSEPSI EFEKTIVITAS PENGENDALIAN ANGGARAN GENERASI Z DENGAN LITERASI KEUANGAN SEBAGAI VARIABEL MODERASI (Pendekatan Teori Mental Accounting) - Ray Marvel Rolemawa; Siti Mutmainah (Diponegoro Journal of Accounting, 2026)
This study examines the impact of the automatic expense categorization feature in mobile banking on the perception of budget control effectiveness of Generation Z, using financial literacy as a moderating variable under the mental accounting theory approach. Primary data were gathered via online Likert-scale questionnaires distributed to university students in Semarang City. Samples were selected through purposive sampling, and data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. The structural model testing confirmed that the utilization of the automatic categorization feature has a positive effect on the perception of budget control effectiveness by directly reducing cognitive load. Financial literacy also exerts a positive direct effect. However, financial literacy does not moderate the primary relationship. This demonstrates that the practical utility of banking automation is highly inclusive, benefit-driven, and accessible to all users regardless of their financial literacy levels.